Karakterisasi Alginat Sebagai Bahan Setara Dengan Jaringan Lunak Untuk Radioterapi - Taat Guswantoro; Astri Suppa Supratman; Imelda Sakti Asih (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Kristen Indonesia, 2020)
At the time of radiotherapy treatment in addition to cancerous tissue, normal tissue around the cancer will also be exposed to radiation doses, inappropriate radiation doses will cause normal tissue to potentially become new cancers called Organ at Risk (OARs). To minimize OARs by using a device made of soft tissue equivalent material that is placed over the surface of the skin called a bolus. The function of this material ensures an increase in surface dosage, this material is also flexible, easy to form, resistant to temperature changes. One of the materials that is easily formed, not easily deformed, flexible and durable is Alginate, because it is a natural hydrogel extracted from brown seaweed. Alginate that will be used in this research is alginate which is often used by dentists to print dentures. Alginate powder is formed by dough with distilled water, then printed in a mold measuring 11 x 11 cm with a thickness of 5, 7 and 9 mm. The characterization of this alginate gel includes electron density and an increase in surface dose percentage. Electron density is obtained by using CT-Scan to find out CT-Number which is then entered into the equation to obtain electron density, electron density from Alginate is obtained by 0.949 so Alginate can be said to be equivalent to breast tissue and fat tissue. Increasing the percentage of surface dose obtained by using the Linac device, obtained at 10 MeV energy Alginate thickness of 5 mm can increase by 0.50%, thickness of 7 mm can increase 9.97% and 9 mm can increase by 19.64%. At 12 MeV energy, 5 mm Alginate is able to increase 0.36%, 7 mm thickness increases by 6.46% and 9 mm thickness is able to increase by 15.03%. With this result Alginate is a soft tissue equivalent material and is able to increase the percentage of surface doses, so that alginate can be applied as a bolus for radiotherapy. Keywords : Alginate, Electron Density, Percentage of Surface Doses.